Organoids for Personalised Cancer Medicine A Vision Assessment of an Emerging Health Technology - Vogt, Henrik; Gaillard, Maxence; Green, Sara.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book builds on and updates work performed in the HYBRIDA project, funded by the EU to develop an ethical framework for organoid research. Organoids are three-dimensional stem cell constructs that mimic organs of the body or tumours. Patient-derived organoids are envisioned to be grown from individual patients$1 (Btumours and used to tailor the most effective and safest treatments in a new form of personalized medicine. This text offers a critical assessment of this vision from the perspective of philosophy of medicine. The authors present a tailored (3z(Bvision assessment(3y(B, presented as examples of methodological development, and applied to objects. They first analyse and describe the vision of using organoids for personalized cancer medicine, then critically evaluate this vision and finally comment on ethical implications of the epistemological issues and how to handle them. The authors further draw on sources for empirical inquiries. This book presents an exercise in health technology assessment conducted by philosophers. Its core readership are philosophers of medicine and bioethicists interested in personalized medicine and stem cell research.s
Introduction -- Methodological development -- Vision analysis of patient-derived organoids for personalized cancer medicine -- Vision evaluation of patient-derived organoids in the clinic -- Conclusion.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Medicine -- Philosophy; Medicine; Medical Ethics; Technology -- Philosophy; Philosophy of Medicine; Clinical Medicine; Medical Ethics; Philosophy of Technology